Encounter with God An Introduction to Christian worship and practice - Forrester, Duncan B.; Tellini, Gian; McDonald, James I. H. (London T&T Clark International, 2004)
An ecumenical introduction to the study of Christian worship which emphasises the complimentarity of Word and Sacrament and the unity of theology and practice, and considers the place of worship in the modern age. It is especially designed for those, of various traditions, who are preparing for the ministry or who participate regularly in worship and wish to deepen their understanding.
Keywords: Public worship. Liturgics. RELIGION -- Institutions & Organizations. RELIGION -- Christian Rituals & Practice -- Worship & Liturgy